Impact Of Rework On Cost And Time Performance Based On Coimbatore Construction Industry - A. Arun (International Journal of Advanced Science and Technology, 2020)
Rework has become a troublemaker in the construction industry, and it has not been given the required consideration; it contributes to time and cost overruns in the project. Hence, to improve the performance of projects, the study evaluated rework in 52 building projects in India. The factor contributing to rework, which was measured with different work categories, identifies the severity of rework. A questionnaire was self-administered on projects identified, and rework factors were ranked according to the degree of severity. This study develops the rework reporting system, which is used to facilitate information retrieval at any moment and to be used as a learning tool to prevent further rework events on future projects